Influência das condições de laminação a quente nas propriedades mecânicas de um aço ARBL da classe 700 MPa de limite de escoamento - Ailton Ribeiro de Avelar Junior (2013)
In this study was evaluated the influence of hot rolling conditions on an industrial scale (reheating of slabs and finishing temperatures), in the tensile mechanical properties, bending and hardness, of a hot rolled HSLA steel of 700 MPa class of yield strength. The mechanical properties were related to the microstructure, volumetric fractions of the phases and the ferritic grain size obtained in the different conditions evaluated. The main propose of this study was to define the best values of hot rolling temperatures to obtain the specified mechanical properties to this steel. It was found that for the experimental conditions used, the influence of reheating slabs and finishing temperatures in the fraction of ferrite and ferritic grain size was inconclusive. However, the yield and tensile strength values were affected by reheating of slab and finishing temperatures. The total elongation was affected only by reheating slab temperature and the hardness was affected by reheating slab temperature and by the interaction between the two temperatures. This result may be related to the amount of dissolved precipitated and volume fraction of second phase present. For all conditions, the results of the bending tests were satisfactory and met the specifications.